Entertaining entrepreneurs : reality TV's Shark Tank and the American dream in uncertain times - Horowitz, Daniel, 1938- (The University of North Carolina Press, 2020)
"In 2007, with the advent of the Great Recession, tens of millions of Americans faced challenges that threatened their economic and psychological well-being. Central to this recession were the threats to the nexus between family and work, with many forces hollowing out the middle class and greatly weakening the health of the working class. Against this backdrop, the hit reality show Shark Tank premiered in 2009 and provided a version of the 'American Dream' that was modest and even tangible. In a time of economic upheaval, the show has offered visions of ambitious entrepreneurs chasing after this dream, often successfully so. In a time of dystopian circumstances, the show has offered its audience utopian pleasures. Cultural historian Daniel Horowitz ties these two threads together, observing that it is no coincidence that Shark Tank launched when the effects of the Great Recession were widely felt and provides a window into the ways mass media explains the opportunities, traps, and dynamics of capitalism. He examines the pervasive popularity of the cult of the entrepreneur and digs into the entrepreneurial culture genre to explain just how this particular manifestation of capitalist culture distorts economic reality and affects the public's sense of what's possible in the 'American Dream' today"--